2009
DOI: 10.1890/08-1311
|View full text |Cite
|
Sign up to set email alerts
|

Responses of benthic macroinvertebrates to environmental changes associated with urbanization in nine metropolitan areas

Abstract: Responses of benthic macroinvertebrates along gradients of urban intensity were investigated in nine metropolitan areas across the United States. Invertebrate assemblages in metropolitan areas where forests or shrublands were being converted to urban land were strongly related to urban intensity. In metropolitan areas where agriculture and grazing lands were being converted to urban land, invertebrate assemblages showed much weaker or nonsignificant relations with urban intensity because sites with low urban i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(105 citation statements)
references
References 27 publications
6
97
1
1
Order By: Relevance
“…However, research on impacts of human disturbance on aquatic organisms, and relations between water pollution and freshwater biodiversity in China is rather insufficient (Chen et al, 2009). Thereby, the impacts of urbanization and impervious area in watersheds on stream benthic macroinvertebrates have far received comparatively little study in China, while many such studies are found in North American (Wang et al, 1997Carter et al, 2009;Cuffney et al, 2010;King et al, 2011), Australian (Walsh et al, 2001;Davies et al, 2010), and South American (Ometo et al, 2000;Miserendina et al, 2008). Zhang et al (2010a) found that urban and rural land use had significant negative impact on water quality and macroinvertebrate diversity in East River in southern China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on impacts of human disturbance on aquatic organisms, and relations between water pollution and freshwater biodiversity in China is rather insufficient (Chen et al, 2009). Thereby, the impacts of urbanization and impervious area in watersheds on stream benthic macroinvertebrates have far received comparatively little study in China, while many such studies are found in North American (Wang et al, 1997Carter et al, 2009;Cuffney et al, 2010;King et al, 2011), Australian (Walsh et al, 2001;Davies et al, 2010), and South American (Ometo et al, 2000;Miserendina et al, 2008). Zhang et al (2010a) found that urban and rural land use had significant negative impact on water quality and macroinvertebrate diversity in East River in southern China.…”
Section: Introductionmentioning
confidence: 99%
“…The response patterns of macroinvertebrate assemblage metrics to intensity of urbanization has been described as linear (Moore & Palmer, 2005;Cuffney et al, 2010, King et al, 2011, wedge-shaped (Booth, 2005;Paul et al, 2009), or sharply linear-to-gradual (Walsh et al, 2005). The percent of impervious area (PIA) has been widely used as a measure of intensity of urbanization Walsh et al, 2005;Purcell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Walters et al (2009) reported correlations between nutrient levels and baseflow water temperature for different macroinvertebrate community indicators. Cuffney et al (2010) reported conductivity was among the variables showing strong associations with urban intensity, and elsewhere it has been found to be a useful integrator of cumulative urban disturbances on water quality (Wang & Yin, 1997;Wenger et al, 2009). Associated water quality influences, along with reduced baseflow and increased sedimentation leading to the development of stagnant pools and accumulations of organic matter, can contribute to low dissolved oxygen levels in urban streams (Wenger et al, 2009).…”
Section: Relationships With Impervious Areamentioning
confidence: 84%
“…Indeed, in revising the impervious cover model, Schueler et al (2009) proposed a curvilinear relationship that accounted for variability in ecological responses, particularly at the lower end of the imperviousness range. In support of this model, recent analyses across nine metropolitan areas in the USA revealed little evidence of an initial period of resistance by macroinvertebrate communities to urbanisation, leading to the conclusion that previously suggested thresholds of imperviousness area were not protective (Cuffney et al, 2010).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation